PRACTICAL FOUNDATIONS OF THE USE OF AUGMENTED AND VIRTUAL REALITY TECHNOLOGIES IN THE DISCIPLINE «DIGITAL LITERACY» - Karelhan, Н.; Uderbayeva, Н.К.; Ongarbayeva, М.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The education system, from school walls to higher education, has a long history of introducing new technologies in addition to traditional pedagogical me thods. It is also known that schoolchildren and students, even teachers, laptops and smart boards, and many other new technologies have learned on their own. The use of virtual and augmented reality technologies in the educational system, especially in elementary grades, will lead to an increase in the interest of students and radical changes in the classical methods that have been coming for a long time. In order to increase the interest of second-graders in obtaining knowledge, skills, skills and knowledge in the discipline "digital literacy", the article considered a workbook with the use of augmented and virtual reality technologies, covering all sections. In particular, on the topic" computer devices " students can get acquainted with 3D objects, as well as with computer devices on the desktop and watch a video video on the same computer using virtual glasses Oculus Quest. As an experiment, workbooks with the use of new technologies were conducted in two Kazakh general education schools in Kostanay District of Kostanay region. In addition, a practical example of the use of Virtual Reality (VR) and Augmented Reality (AR) technologies in the educational process was considered and the effectiveness was determined.